THE MAIN CHARACTER’S SURVIVAL INSTINCT IN HERBERT GEORGE WELL’S NOVEL THE WAR OF THE WORLDS - Ilham Ilham; Sumarwati K. Poli; Mustafa Makka (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2019)
One of the most interesting aspects of The War of the Worlds is the way in which the Martians are described, and the manner with which they take over the world. The aims of the study were to reveal the survival instinct of the main character in the novel “The War of The Worlds” of Herbert George Wells’s work, and how changes in behavior and the main character was currently in a state of urgency to survive. This study employed qualitative descriptive study with psychoanalytical approach initiated by Sigmund Freud, focused on literature as a reflection of real life. This research data were collected from the novel “The War of The Worlds” (1898). The study revealed that survival instinct of the main character of novel came from basic instincts, life instinct (Eros) and death instinct (Thanatos) according to Sigmund Freud’s theory. The Martians described as aliens invaded earth much more sophisticated than human, which made the main character who just a civil society striving to stay alive. The Martians had only one purpose, to destroy all humans and take over the planet. During The Martians invasion, the main character was not only trying to survive but also strived for source of food and water. In his effort to stay alive, the main character in the novel The War of The Worlds (1898) had to kill others to guarantee he stayed alive. Being trapped in regret and despair, he decided to end his own life, but something strange happened to The Martians, they were killed by bacteria. Human were immune to the bacteria, but The Martians from Mars were not and eventually died.